META-ANALISIS: PENGARUH AUDIT INTERNAL TERHADAP KINERJA PERGURUAN TINGGI - Intan Widia Sari; Dian Anita Nuswantara (Journal of Innovation Research and Knowledge, 2023)
Abstract: This study aims to reconcile conflicting empirical result from prior studies on the association between internal audit and higher education performance. Furthermore, this study also investigates whether the conficting findings were moderated by the different higher education performance measures. This study used meta-analysis to integrate the previous studies findings on the association between intenal audit and higher education performance and further investigated the moderators of such association. The findings showed that internal audit ihave a association with higher education performance, but that association is not moderated by differences in higher education performance measures. Keywords: Meta-Analysis, Internal Audit, Higher Education Performance